DIDACTIC REQUIREMENTS FOR MODELING AN INNOVATIVE INFORMATION EDUCATIONAL ENVIRONMENT IN TEACHING WORLD HISTORY - Umirzoq Yuldashev (European Science Publishing, 2024)
This article discusses the modeling of an innovative information educational environment in the teaching of world history and its significance for enhancing educational effectiveness. The possibilities of individualizing the learning process through innovative technologies, interactivity and collaboration, flexibility, and providing rich educational materials are analyzed. Additionally, the didactic requirements that need to be considered when modeling an innovative information educational environment are highlighted.
Keywords: Innovative technologies, information educational environment, didactic requirements, world history, individualization, interactivity, collaboration, flexibility.